Chuckrow's theory of the prenatal origin of music. (December 2019) - Parncutt, Richard; Chuckrow, Robert
In 1965, the second author, a graduate student in physics at New York University, drafted a paper entitled "Music: A synthesis of prenatal stimuli, " in which he proposed that structural elements of music such as rhythm and melody are analogs of fetal stimuli. In the 1980s, the first author independently published a similar theory. Both authors considered fetal perception of internal body sounds, correlations between those sounds and maternal states, the ability of the fetus to hear and remember sound patterns, biological and behavioral correlates of emotions shared by mother and fetus, transfer of hormones across the placenta, and effects of maternal psychopathology on infant behavior. Both argued that consideration of fetal consciousness is unnecessary because unconscious learning can influence later conscious behaviors and experiences. Chuckrow uniquely proposed that meter and polymeter, perceived as combinations of approximately isochronous pulses with one pulse in the foreground, might derive from the combined sound of maternal and fetal heartbeats as perceived by the fetus. We evaluate these theories in the context of more recent approaches to the origin of music. A systematic consideration of prenatal influences can parsimoniously explain communicative, emotional and structural aspects of music. Music may be a by-product of adaptations such as prenatal hearing and motherese that promoted infant survival in ancient hunter-gatherer settings.